Attainment of "Project Management and Finance" Graduate Attribute (GA) for Post Graduate Program in Engineering through Course Project - Kulkarni, Vinayak; Gaitonde, V. N.; Mench, R. G. (Journal of Engineering Education Transformations, 2016)
The National Board of Accreditation (NBA) in India has specified specific graduate attributes for post graduate program in engineering. In B V B College of Engineering & Technology, Hubballi, the Production Management PG program has made an attempt to design and conduct the course project from last two academic years in the core course "Project Management" at 1st semester level, which has been designed to address the graduate attribute 7 related to "Project Management and Finance". Based on this the program outcome for our PG program is defined as "Ability to carry feasibility study and evaluate projects considering economical and financial factors". Keeping this outcome in mind, the course project has been conducted addressing feasibility study, economical and financial factors as mentioned in attribute 7. The students were made to work on this course project for the duration of 12 weeks, which included activities like industrial visit, literature review, preliminary study, feasibility study, facets analysis, report submission and oral presentation. The evaluation process for this course project was rubrics based consisting of two different outcome elements and related performance indicators to address particularly the graduate attribute-7. The work carried out by the students focuses completely on the analysis of facets of projects from marketing analysis to ecological analysis. The conduct of course project in the core course like project management really differentiates the learning of post graduate level to that of undergraduate level as more work is being carried on the analysis part during the process of course project. The percentage attainment of each outcome element addressing the attribute-7 for both the academic years i.e 2013-14 and 2014-15 has been compared.